How do non-emergency medical transportation services influence patients’ subjective well-being? - Maryam Yousefibaseri; Yi-Ling Cheng; Jane Lin (Transportation Research Part D: Transport and Environment, 2026)

Treated wastewater irrigation reshapes rhizosphere microbial communities through salinity-driven soil changes - Lin Wang; Caroline de Tender; Lisa Joos; Tim De Cuypere; Bert Everaert; Sarah Ommeslag; Jane Debode; Sarah Garré; Wim Cornelis (Applied Soil Ecology, 2026)

Dietary Patterns Associated With Weight Loss Among Patients With Colorectal Cancer During the First 6 Months After Diagnosis: A Cross-Sectional Analysis From the ColoCare Study - Rachel Hoobler; Fred K. Tabung; Tengda Lin; Biljana Gigic; Kristen S. Smith; Kary Woodruff; Sylvia L. Crowder; Sheetal Hardikar; Doratha A. Byrd; Adriana M. Coletta; Alejandro Sanchez; Amandine Chaix; et al. (Journal of the Academy of Nutrition and Dietetics, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

PROMETHEUS clinical trial protocol: tailoring healthy ageing with lifestyle and nutraceuticals - Ajla Hodzic Kuerec; Lihuan Guan; Weilan Wang; Duarte Barros; Wejdan M. Alenezi; Jozo Grgic; Vanessa K. Wazny; Jordi Morwani-Mangnani; Mazzarine Dotou; Dingding Zhang; Tong Chen; Jiaqiu Wang; et al. (GeroScience, 2026)
The d emographic shift toward an older population is accelerating the prevalence of age-related diseases. Precision geromedicine represents a paradigm shift in targeting the biological processes of ageing to optimise health and healthspan, which likely requires multimodal tailored interventions. PROMETHEUS, as part of the XPRIZE healthspan semi-finalist competition, is an 8-week feasibility and exploratory study including 20 middle-aged-to-older participants who received a multimodal intervention comprising fundamental and augmented interventions. The fundamental interventions include sleep and dietary recommendations; supplementation with whey protein, creatine, and fucoidan; supervised exercise with an exergaming component (dual-task cognitive-physical training); motivational interviewing; and cognitive behavioural therapy. The augmented intervention is further personalised based on predefined gerotypes, reflecting individual ageing patterns beyond chronological age. At baseline, urolithin A, nicotinamide mononucleotide, and/or multivitamin-multimineral were prescribed to participants based on their muscle mass, VO 2 peak, and cognitive performance. At mid-intervention, interventions were adjusted based on individual response, including dose escalation and/or the addition of ergothioneine for inadequate improvement in cognition. Primary outcomes include measures of muscle strength and mass, immune function and cognitive performance, and feasibility indicators such as adherence and trial completion. Secondary outcomes include assessments of other biological, clinical, and digital biomarkers of ageing, as well as qualitative indicators of motivation and personal values. This study is aimed at investigating the recruitment feasibility, safety, adherence, and exploratory outcome trajectories of a multimodal, personalised precision geromedicine intervention protocol based on individual participant’s baseline characteristics and interim responses. These findings will also inform the design of a subsequent 12-month, randomised controlled trial evaluating personalised lifestyle and nutraceutical strategies with the potential to incorporate repurposed pharmacological agents to optimise age-related health outcomes.

An alternative last-mile delivery system: Leveraging microhubs and crowdshipping - Amir Shafiee; Hanieh Rastegar Moghaddam; Sudheer Ballare; Jane Lin (Transportation Research Part D: Transport and Environment, 2026)

Powering long haul freight: hydrogen refueling station siting using pipeline infrastructure - Jialu Yang; Danesh Hosseinpanahi; Bo Zou; Jane Lin (Transportation Research Part D: Transport and Environment, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Effective metal recovery from lithium-ion battery waste using a ternary deep eutectic solvent in a high solid-to-liquid ratio under mild and ambient conditions - Hsin-Jou Cheng; Yi-Jane Lin; Shu-Chi Chang; Shih-Yen Yang; Ting-Wei Lee; Chiaying Chen (Journal of Environmental Chemical Engineering, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Prenatal exposure to extreme heat and autism in children - David G. Luglio; Xin Yu; Jane C. Lin; Ting Chow; Mayra P. Martinez; Zhanghua Chen; Sandrah P. Eckel; Joel Schwartz; Frederick W. Lurmann; Nathan Pavlovic; Rob McConnell; Anny H. Xiang; et al. (Science of The Total Environment, 2026)

Pre-surgery gut microbial diversity and abundance are associated with post-surgery onset of cachexia in colorectal cancer patients: the ColoCare Study - Mmadili N. Ilozumba; Maria F. Gomez; Tengda Lin; Caroline Himbert; June L. Round; W. Zac Stephens; Christy A. Warby; Sheetal Hardikar; Christopher I. Li; Jane C. Figueiredo; Victoria Damerell; Gary C. Fillmore; et al. (Cancer Causes & Control, 2025)
Background Cachexia accounts for about 20% of all cancer-related deaths and it is indicative of poor prognosis and progressive functional impairment. The role of the gut microbiome in the development of cachexia in colorectal cancer (CRC) patients has not been established. Methods Pre-surgical stool samples from n = 103 stage I–III CRC patients in the ColoCare Study were analyzed using 16S rRNA gene sequencing (Illumina) to characterize fecal bacteria. We calculated estimates of alpha- and beta-diversity and a priori- and exploratory-selected bacterial relative abundance. Using Fearon criteria, cachexia onset at 6 months post-surgery was defined as > 5% weight loss over the past 6 months and/or body mass index (BMI) of < 20 kg/m 2 and weight loss of > 2%. Associations of microbial metrics with cachexia onset were estimated using multivariable logistic regression models. Results Higher alpha-diversity was positively associated with cachexia onset, with stronger associations in females, patients < 65 years, those receiving adjuvant treatment, consuming high fiber, or with energy intake outside USDA recommendations ( p < 0.05). Porphyromonas (OR = 0.51, 95% CI 0.26–0.89, p = 0.03) and Actinomyces (OR = 0.72, 95% CI 0.48–1.03, p = 0.08) were inversely associated with cachexia, although the association for Actinomyces did not reach statistical significance. Stratified analyses revealed a stronger inverse association between Porphyromonas and cachexia onset in males, patients with rectal or stage III tumors, those receiving neoadjuvant treatment, physically inactive individuals, and those consuming low fiber. However, these associations did not reach statistical significance (0.05 ≤ p < 0.10). Conclusion Higher gut microbial alpha-diversity and lower relative abundances of the genera Porphyromonas and Actinomyces in pre-surgery stool samples were associated with onset of cachexia in CRC patients six months post-surgery. This is the first study to explore a link between the gut microbiome and cachexia in CRC patients, providing novel insights into the biology of cachexia and potential clinical interventions.

Toward resilient logistics electrification: Assessing diesel-to-electric fleet transition under variable temperatures - Hanieh Rastegar Moghaddam; Amir Shafiee; Jane Lin (Transportation Research Part D: Transport and Environment, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Characteristics and sources of volatile organic compounds and their impacts on ozone formation in a coastal city of southeastern China - Chende Gai; Chuanyou Ying; Xugeng Cheng; Fei Jiang; Jing Lin; Zhixiong Chen; Lei Shu; Jun Hu; Dongsheng Jiang; Mengmiao Yang; Jane Liu (Atmospheric Pollution Research, 2025)

Lactiplantibacillus plantarum GMNL-661 Ameliorates Clostridioides difficile Infection and Reconfigures Intestinal Microbiota in a Murine Model - Meng-Jia Li; Hong-Ming Chen; Yueh-Lin Chen; Yi-Hsin Lai; Cheng-Yu Lai; Jhen-Wei Ruan; Jenn-Wei Chen; Wan-Hua Tsai; Wen-Chien Ko; Pei-Jane Tsai (Probiotics and Antimicrobial Proteins, 2025)

Discordant sibling analysis of autism risk associated with prenatal exposure to tailpipe and non-tailpipe particulate matter pollution - Anny H. Xiang; Jane C. Lin; Ting Chow; Xin Yu; Mayra P. Martinez; Zhanghua Chen; Sandrah P. Eckel; Joel Schwartz; Frederick W. Lurmann; Michael J. Kleeman; Rob McConnell; Md. Mostafijur Rahman (Environmental Research, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Decomposing the variance: The unique and shared associations of fine and ultrafine particulate matter exposed during pregnancy with child autism spectrum disorder - Xin Yu; Michael J. Kleeman; Jane C. Lin; Ting Chow; Mayra P. Martinez; Zhanghua Chen; Jiu-Chiuan Chen; Sandrah P. Eckel; Joel Schwartz; Frederick W. Lurmann; Rob McConnell; Anny H. Xiang; et al. (Science of The Total Environment, 2024)

Mapping new psychoactive substances: Leveraging GIS technology for advanced global surveillance and policy support - Ting-Jung Ku; Tien-Chueh Kuo; Olivia A. Lin; Yufeng Jane Tseng (Regulatory Toxicology and Pharmacology, 2024)

Exploring characteristics of waxy wheat starches cross-linked at low levels: Insights from pasting, rheological, and textural properties - Zhonghua Gu; Xianying Sha; Xinwei Wang; Renyong Zhao; Reham Khashaba; Jay-lin Jane; Hongxin Jiang (Food Bioscience, 2024)

Postvaccination serosurveillance of foot-and-mouth disease through virus-neutralizing and nonstructural protein antibody tests on pig farms in Taiwan: 2009–2020 - Ming-Chang Lee; Yu-Fen Sun; Ming-Chung Deng; Nien-Nung Lin; Jung-Pin Hsu; Chwei-Jang Chiou; Wen-Jane Tu; Shih-Ping Chen (Preventive Veterinary Medicine, 2024)

Is electric truck a viable alternative to diesel truck in long-haul operation? - Xi Cheng; Jane Lin (Transportation Research Part D: Transport and Environment, 2024)

Progress in understanding resistant-starch formation in hydroxypropyl starch: A minireview - Hongxin Jiang; Yaping Feng; Jay-lin Jane; Yunfei Yang (Food Hydrocolloids, 2024)

Morphology and chemical composition of Taiwan oil millet (Eccoilopus formosanus) epicuticular wax - Marita Anggarani; Yu-Ying Lin; Shao-An Fang; Hshin-Ping Wu; Chi-Chih Wu; Wann-Neng Jane; Thomas James Roscoe; Frederic Domergue; Yue-Ie Caroline Hsing (Planta, 2024)

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Assessing fusarium oxysporum disease severity in cotton using unmanned aerial system images and a hybrid domain adaptation deep learning time series model - Alwaseela Abdalla; Terry A. Wheeler; Jane Dever; Zhe Lin; Joel Arce; Wenxuan Guo (Biosystems Engineering, 2024)

Historical biomonitoring of pollution trends in the North Pacific using archived samples from the Continuous Plankton Recorder Survey - Kefeng Li; Jane C. Naviaux; Sai Sachin Lingampelly; Lin Wang; Jonathan M. Monk; Claire M. Taylor; Clare Ostle; Sonia Batten; Robert K. Naviaux (Science of The Total Environment, 2023)

Comparison of controlled drugs and new psychoactive substances (NPS) regulations in East and Southeast Asia - Olivia A. Lin; Pei-Jiun Chuang; Y. Jane Tseng (Regulatory Toxicology and Pharmacology, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Determinants of blood and saliva lead concentrations in adult gardeners on urban agricultural sites - Lindsay Bramwell; Jackie Morton; Anne-Helen Harding; Nan Lin; Jane Entwistle (Environmental Geochemistry and Health, 2022)
Soil Pb concentrations at urban agriculture sites (UAS) commonly exceed recommended safe levels. There is a lack of evidence regarding uptake of Pb by gardeners using such sites for food crops. Our study aimed to elucidate whether gardening in soil with raised Pb levels results in Pb body burdens of concern to health, and to assess confounding factors influencing Pb body burden. Our cross-sectional case study measured Pb in saliva and blood of UAS gardeners (n = 43), soil and produce samples from their UAS, and home tap water. Blood and saliva Pb concentrations were compared with those from non-UAS gardener controls (n = 29). A health risk threshold of 5 µg dL −1 blood Pb level (BLL) was selected in keeping with international guidance. Detailed surveys investigated individuals’ anthropometrics and potential Pb exposures from diet, and historic and everyday activities. Saliva was not found to be a suitable biomarker of adult Pb exposure in this context. Predictors of higher BLLs were being older, being male and eating more root vegetables and shrub fruit. Eating more green vegetables predicted a lower BLL, suggesting a protective effect against Pb uptake. UAS gardeners’ BLLs (geometric mean 1.53; range 0.6–4.1 µg dL −1 ) were not significantly higher ( p = 0.39) than the control group (geometric mean 1.43; range 0.7–2.9 µg dL −1 ). All BLLs were below 5 µg dL −1 except one resulting from occupational exposure. Having paired the UAS gardeners with closely matched controls, we found Pb in UAS soils (with range 62–1300 mg kg −1 from common urban sources) unlikely to pose an additional risk to adult health compared to their neighbours who did not access UAS. As such, other Pb sources may be the dominant factor controlling BLL.

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Trichome Lengths of the Heterocystous N2-Fixing Cyanobacteria in the Tropical Marginal Seas of the Western North Pacific - Sing-how Tuo; Margaret R. Mulholland; Yukiko Taniuchi; Houng-Yung Chen; Wann-Neng Jane; Yen-Huei Lin; Yuh-ling Lee Chen (Frontiers in Marine Science, 2021)
Calothrix rhizosoleniae and Richelia intracellularis are heterocystous cyanobacteria found in the tropical oceans. C. rhizosoleniae commonly live epiphytically on diatom genera Chaetoceros ( C-C ) and Bacteriastrum ( B-C ) while R. intracellularis live endosymbiotically within Rhizosolenia ( R-R ), Guinardia ( G-R ), and Hemiaulus ( H-R ); although, they occasionally live freely (FL- C and FL- R ). Both species have much shorter trichomes than the other marine filamentous cyanobacteria such as Trichodesmium spp. and Anabaena gerdii . We investigated the trichome lengths of C. rhizosoleniae and R. intracellularis in the South China Sea (SCS) and the Philippine Sea (PS) between 2006 and 2014. On average, H-R had the shortest trichome lengths (3.5 cells/trichome), followed by B-C and C-C (4.9–5.2 cells/trichome) and FL- C (5.9 cells/trichome), and R-R , G-R , and FL- R had the longest trichome lengths (7.4–8.3 cells/trichome). Field results showed the trichome lengths of C-C and B-C did not vary seasonally or regionally. However, FL- C and H-R from the SCS and during the cool season had longer trichomes, where/when the ambient nutrient concentrations were higher. R-R , G-R , and FL- R also showed regional and seasonal variations in trichome length. Ultrastructural analysis found no gas vesicles within the C. rhizosoleniae cells to assist in buoyancy regulation. Results suggest that the trichome lengths of C. rhizosoleniae and R. intracellularis might be regulated by their diatom hosts’ symbiotic styles and by ambient nutrients. Short trichome length might help C. rhizosoleniae and R. intracellularis to stay in the euphotic zone regardless as to whether they are free-living or symbiotic.

Correction to: Shared genetic architecture between metabolic traits and Alzheimer’s disease: a large-scale genome-wide cross-trait analysis - Zhaozhong Zhu; Yifei Lin; Xihao Li; Jane A. Driver; Liming Liang (Human Genetics, 2021)

A Millifluidic Perfusion Cassette for Studying the Pathogenesis of Enteric Infections Using Ex-Vivo Organoids - Reid L. Wilson; Sarah A. Hewes; Anubama Rajan; Shih-Ching Lin; Carolyn Bomidi; Takanori Iida; Mary K. Estes; Anthony W. Maresso; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2021)

A lack of association between increases in gastrointestinal, liver, and urologic cancers and cyanobacterial contamination of fresh water lakes in Manitoba - Meaghan A. Labine; Emma Shu; Lin Xue; Giselle Mak; Jane Griffith; Gerald Y. Minuk (Environmental Science and Pollution Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Tropical cyclone sensitivities to CO2 doubling: roles of atmospheric resolution, synoptic variability and background climate changes - Gabriel A. Vecchi; Thomas L. Delworth; Hiroyuki Murakami; Seth D. Underwood; Andrew T. Wittenberg; Fanrong Zeng; Wei Zhang; Jane W. Baldwin; Kieran T. Bhatia; William Cooke; Jie He; Sarah B. Kapnick; et al. (Climate Dynamics, 2019)

Shared genetic architecture between metabolic traits and Alzheimer’s disease: a large-scale genome-wide cross-trait analysis - Zhaozhong Zhu; Yifei Lin; Xihao Li; Jane A. Driver; Liming Liang (Human Genetics, 2019)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Effects of doping amounts of potassium ferricyanide with titanium dioxide and calcination durations on visible-light degradation of pharmaceuticals - Justin Chun-Te Lin; Mark Daniel G. de Luna; Mary Jane N. Gotostos; Ming-Chun Lu (Environmental Science and Pollution Research, 2016)

Novel characteristics of a carbohydrate-binding module 20 from hyperthermophilic bacterium - Il-Nam Oh; Jay-lin Jane; Kan Wang; Jong-Tae Park; Kwan-Hwa Park (Extremophiles, 2015)

Smoking, alcohol, diabetes, obesity, socioeconomic status, and the risk of colorectal cancer in a population-based case–control study - Terry Boyle; Lin Fritschi; Seyed Mehdi Tabatabaei; Kathrin Ringwald; Jane S. Heyworth (Cancer Causes & Control, 2014)

pIMP-PH114 Carrying bla IMP-4 in a Klebsiella pneumoniae Strain is Closely Related to Other Multidrug-Resistant IncA/C2 Plasmids - Pak-Leung Ho; Wai-U Lo; Jane Chan; Yuk-Yam Cheung; Kin-Hung Chow; Wing-Cheong Yam; Chi-Ho Lin; Tak-Lun Que (Current Microbiology, 2014)

The California Breast Cancer Survivorship Consortium (CBCSC): prognostic factors associated with racial/ethnic differences in breast cancer survival - Anna H. Wu; Scarlett Lin Gomez; Cheryl Vigen; Marilyn L. Kwan; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2013)

Ectopic expression of bacterial amylopullulanase enhances bioethanol production from maize grain - Hartinio N. Nahampun; Chang Joo Lee; Jay-Lin Jane; Kan Wang (Plant Cell Reports, 2013)

Quantitative exposure metrics for sleep disturbance and their association with breast cancer risk - Jennifer Girschik; Lin Fritschi; Thomas C. Erren; Jane Heyworth (Cancer Causes & Control, 2013)

Spatial relationships between lead sources and children’s blood lead levels in the urban center of Indianapolis (USA) - Deborah Morrison; Qing Lin; Sarah Wiehe; Gilbert Liu; Marc Rosenman; Trevor Fuller; Jane Wang; Gabriel Filippelli (Environmental Geochemistry and Health, 2013)

Pseudomonas aeruginosa isolates of distinct sub-genotypes exhibit similar potential of antimicrobial resistance by drugs exposure - Zhen-Hong Liu; Yan Xu; Li-Bo Duo; Yu Liu; Zhao-Zhen Xu; Jane L. Burns; Gui-Rong Liu; Bao-Feng Yang; Shu-Lin Liu (Antonie van Leeuwenhoek, 2013)

Fabrication and Mechanical Evaluation of Anatomically-Inspired Quasilaminate Hydrogel Structures with Layer-Specific Formulations - Hubert Tseng; Maude L. Cuchiara; Christopher A. Durst; Michael P. Cuchiara; Chris J. Lin; Jennifer L. West; K. Jane Grande-Allen (Annals of Biomedical Engineering, 2013)

Resistance training and the risk of colon and rectal cancers - Terry Boyle; Fiona Bull; Lin Fritschi; Jane Heyworth (Cancer Causes & Control, 2012)

Timing and intensity of recreational physical activity and the risk of subsite-specific colorectal cancer - Terry Boyle; Jane Heyworth; Fiona Bull; Sarah McKerracher; Cameron Platell; Lin Fritschi (Cancer Causes & Control, 2011)

Idebenone inhibition of glutamate release from rat cerebral cortex nerve endings by suppression of voltage-dependent calcium influx and protein kinase A - Yi Chang; Yu-Wan Lin; Su-Jane Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Bacteria associated with an encrusting sponge ( Terpios hoshinota ) and the corals partially covered by the sponge - Sen‐Lin Tang; Mei‐Jhu Hong; Ming‐Hui Liao; Wann‐Neng Jane; Pei‐Wen Chiang; Chung‐Bin Chen; Chaolun A. Chen (Environmental Microbiology, 2011)
Summary Terpios hoshinota , a dark encrusting sponge, is known to be a competitor for space in coral reef environments, and facilitates the death of corals. Although numerous cyanobacteria have been detected in the sponge, little is known of the sponge‐associated bacterial community. This study examined the sponge‐associated bacterial community and the difference between the bacterial communities in the sponge and the coral partially covered by the sponge by analysis of 16S rRNA gene sequences of samples isolated from the sponge covering the corals Favia complanata, Isopora palifera, Millepora sp. , Montipora efflorescens and Porites lutea . The sponge‐associated bacterial community was mainly (61–98%) composed of cyanobacteria, with approximately 15% of these alphaproteobacteria and gammaproteobacteria, although the proportions varied in different sponge samples. The dominant cyanobacteria group was an isolated group closely related to Prochloron sp. The comparison of the bacterial communities isolated from sponge‐free and the sponge‐covered P. lutea showed that covering by the sponge caused changes in the coral‐associated bacterial communities, with the presence of bacteria similar to those detected in black‐band disease, suggesting the sponge might benefit from the presence of bacteria associated with unhealthy coral, particularly in the parts of the coral closest to the margin of the sponge.

Health behaviors of cancer survivors: data from an Australian population-based survey - Elizabeth G. Eakin; Danny R. Youlden; Peter D. Baade; Sheleigh P. Lawler; Marina M. Reeves; Jane S. Heyworth; Lin Fritschi (Cancer Causes & Control, 2007)

Prevention of TGF-β-induced apoptosis by interlukin-4 through Akt activation and p70S6K survival signaling pathways - Sue-Jane Lin; Chungming Chang; Ah-Kau Ng; Shu-Han Wang; Jia-Je Li; Cheng-po Hu (Apoptosis, 2007)

Chloroplast genome aberration in micropropagation-derived albino Bambusa edulis mutants, ab1 and ab2 - Nien-Tsu Liu; Wann-Neng Jane; Hsin-Sheng Tsay; Hui Wu; Wei-Chin Chang; Choun-Sea Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Streptococcal pyrogenic exotoxin B causes mitochondria damage to polymorphonuclear cells preventing phagocytosis of Group A streptococcus - Chuan Chiang-Ni; Chih-Hung Wang; Pei-Jane Tsai; Woei-Jer Chuang; Yee-Shin Lin; Ming-T. Lin; Ching-Chuan Liu; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2006)

Using Redox Potential to Detect Microbial Activities During Clavulanic Acid Biosynthesis in Streptomyces clavuligerus - Yun-Huin Lin; Sz-Chwun John Hwang; Jian Tong Gong; Jane-Yii Wu; Kuo-Cheng Chen (Biotechnology Letters, 2005)

Hydrophilic excipients modulate the time lag of time-controlled disintegrating press-coated tablets - Shan-Yang Lin; Mei-Jane Li; Kung-Hsu Lin (AAPS PharmSciTech, 2004)

Formulation design of double-layer in the outer shell of dry-coated tablet to modulate lag time and time-controlled dissolution function: Studies on micronized ethylcellulose for dosage form design (VII) - Shan-Yang Lin; Kung-Hsu Lin; Mei-Jane Li (The AAPS Journal, 2004)

Calcium-antagonizing activity of S -petasin, a hypotensive sesquiterpene from Petasites formosanus , on inotropic and chronotropic responses in isolated rat atria and cardiac myocytes - Guei-Jane Wang; Jyh-Fei Liao; Kadon K. Hintz; Chuen-Chao Shi; Chieh-Fu Chen; Wen-Pin Chen; Ming-Jai Su; Yun-Lian Lin; Jun Ren (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

The reinstatement model of drug relapse: history, methodology and major findings - Yavin Shaham; Uri Shalev; Lin Lu; Harriet de Wit; Jane Stewart (Psychopharmacology, 2003)

The Student Watershed Research Project (SWRP): collecting watershed data for use by resource management agencies - Deborah J. Lev; Stacy L. Renfro; D. Torrey Lindbo; Wes Jarrell; Jane Blair; Steve Andrews; Lin Howell (Urban Ecosystems, 1998)

Effects of zinc supplementation on the plasma glucose level and insulin activity in genetically obese (ob/ob) mice - Ming-Der Chen; Shy-Jane Liou; Pi-Yao Lin; Vivian C. Yang; Paul S. Alexander; Wen-Han Lin (Biological Trace Element Research, 1998)